2020
DOI: 10.1002/jcla.23450
|View full text |Cite
|
Sign up to set email alerts
|

Screening and identification of biomarkers associated with the diagnosis and prognosis of lung adenocarcinoma

Abstract: Background In this study, we aimed to identify the pathogenesis and prognostic biomarkers of lung adenocarcinoma (LUAD). Methods Differentially expressed mRNAs (DEmRNAs) and single nucleotide polymorphism (SNP) mutant genes were screened. In addition, enrichment and protein‐protein interaction (PPI) network analyses of the SNP‐mutated genes were performed. Thereafter, the correlation between gene mutation and expression was analyzed. Finally, the mutated genes associated with LUAD prognosis were validated on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The other published finding concerning breast cancer is that the somatic SEMA6D mutations that were predicted to cause loss of gene function were identified in early onset breast cancers [ 51 ], a cancer type that is typically aggressive, frequently triple-negative, and associated with poor outcomes; this result, again, is potentially compatible with our finding that lower SEMA6D expression was associated with poorer outcomes. Some support is also available from other cancers; for example, in lung cancer, which is also invariably treated with cytotoxic chemotherapy, somatic SEMA6D mutations were found that reduced SEMA6D expression, and low SEMA6D expression was associated with poor outcomes [ 52 ]. In terms of mechanisms, it is challenging to speculate since it has not even been determined in these cells whether SEMA6D is working as a ligand for plexins, or as a receptor in its own right, therefore a multitude of potential down-stream signaling pathways exist [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The other published finding concerning breast cancer is that the somatic SEMA6D mutations that were predicted to cause loss of gene function were identified in early onset breast cancers [ 51 ], a cancer type that is typically aggressive, frequently triple-negative, and associated with poor outcomes; this result, again, is potentially compatible with our finding that lower SEMA6D expression was associated with poorer outcomes. Some support is also available from other cancers; for example, in lung cancer, which is also invariably treated with cytotoxic chemotherapy, somatic SEMA6D mutations were found that reduced SEMA6D expression, and low SEMA6D expression was associated with poor outcomes [ 52 ]. In terms of mechanisms, it is challenging to speculate since it has not even been determined in these cells whether SEMA6D is working as a ligand for plexins, or as a receptor in its own right, therefore a multitude of potential down-stream signaling pathways exist [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…BUB1, BUB1B, PLK1, and CDC20 were suggested as LUAD stem cell biomarkers (60). CENPF, KIF2C, CDK1, ASPM, and MYH10 were also proposed as diagnosis and prognosis biomarkers of LUAD (61)(62)(63)(64)(65)(66). CDKN3 was not yet reported as a diagnosis or prognosis biomarker but expected to be a promising therapeutic target in LUAD (63).…”
Section: Discussionmentioning
confidence: 99%
“… 12 On the other hand, in lung adenocarcinoma, SEMA6D expression was downregulated, and lower SEMA6D levels were associated with shorter overall survival indicating a tumor suppressor role in the lung. 13 Altogether, the data suggest a context-dependent role for SEMA6D in tumorigenesis.…”
Section: Introductionmentioning
confidence: 83%